Pasar Modal Syariah - Maryani (Fakultas Ekonomi dan Bisnis Islam, 2015)
In Islam investment is highly recommended muamalah activity, because by investing assets held to be productive and also bring benefits to others. Many people choose to invest in the form of investment. One form of investment is embed their wealth in the stock market. The capital market is basically a market for a variety of financial instruments or securities that can be traded long-term, either in the form of debt or equity capital. The capital market is one of the important pillars of the world economy today. With the presence of the Islamic capital market, provide an opportunity for Muslims and non-Muslims who want to invest their funds in accordance with Islamic principles that provide serenity and confidence in the transaction is lawful.